Perhitungan Angka Lempeng Total (ALT) dan Identifikasi Keberadaan Bakteri Escherichia coli pada Mie Basah yang Dijual di Pasar Segiri Kota Samarinda - Khatimah, Khusnul; Purwati, Sri; Rambitan, Vandalita Maria Magdalena; Serena, Nelda Anasthasia (Biocaster : Jurnal Kajian Biologi, 2025)
Microbiological contamination is one of the factors that affect food safety, especially in wet noodles which have a high moisture content so they are easily damaged. This study aims to determine the number of Total Plate Numbers (ALT) and identify the presence of Escherichia coli in wet noodles sold at Segiri Market, Samarinda City. The research was carried out using a descriptive analytical method through laboratory testing of five wet noodle samples taken by purposive sampling. ALT testing uses the pour plate method on Plate Count Agar (PCA) media, while Escherichia coli testing is carried out by the Most Probable Number (MPN) method followed by confirmation on Eosin Methylene Blue Agar (EMBA) media. The results of the ALT test showed that two samples met the maximum limit of ALT according to SNI 2987:2015 (≤1.0 × 106 colonies/g), while three samples exceeded the threshold. The MPN test showed that four samples were below the maximum limit according to SNI 2987:2015 (≤10 APM/g) and one sample exceeded the threshold. The EMBA confirmation showed two positive samples of Escherichia coli. These results confirm the importance of applying hygienic practices in the processing, storage, and packaging to reduce the risk of microbiological contamination.